Future research tendencies for solar energy management using a bibliometric analysis, 2000–2019 - David, Thamyres Machado [UNESP]; Silva Rocha Rizol, Paloma Maria [UNESP]; Guerreiro Machado, Marcela Aparecida [UNESP]; Buccieri, Gilberto Paschoal [UNESP] (Elsevier, 2020)
Using the Scopus database between the years of 2000 and 2019, a bibliometric study was done to analyze the scientific publications in the area of photovoltaic solar energy management. From the preliminary analysis of future research tendencies, ten possibilities of study topics were developed; and due to that it was possible to assume that even though many studies of technological development are found, some insights can still be approached in a way that the practical implementation of solar systems photovoltaic is better used. This data was validated by the analysis performed with the Scimat scientific mapping software under a longitudinal structure, verifying the future tendencies researches mentioned previously.
Keywords: Bibliometry; Energy; Energy management; Green engineering; Photovoltaic solar energy; Solar energy; Sustainable development